Three‐Dimensional Time‐Lapse Geoelectrical Monitoring of Water Infiltration in an Experimental Mine Waste Rock Pile - Dimech, A. (2020)
Open‐pit mines often generate large quantities of waste rocks that are usually stored in waste rock piles (WRPs). When the waste rocks contain reactive minerals (mainly sulfides), water and air circulation can lead to the generation of contaminated drainage. An experimental WRP was built at the Lac Tio mine (Canada) to validate a new disposal method that aims to limit water infiltration into reactive waste rocks. More specifically, a flow control layer was placed on top of the pile, which represents a typical bench level, to divert water toward the outer edge. Hydrogeological sensors and geophysical electrodes were installed for monitoring moisture distribution in the pile during infiltration events. A three‐dimensional (3D) time‐lapse hydrogeophysical monitoring program was conducted to assess water infiltration and movement. Readings from the 192 circular electrodes buried in the WRP were used to reconstruct the 3D bulk electrical resistivity (ER) variations over time. A significant effort was devoted to assessing the spatiotemporal evolution of water ER because the bulk ER is strongly affected by water quality (and content). The water ER was used as a tracer to monitor the infiltration and flow of resistive and conductive waters. The results indicate that the inclined surface layer efficiently diverts a large part of the added water away from the core of the pile. Local and global models of water infiltration explaining both bulk and water ER variations are proposed. The results shown here are consistent with hydrogeological data and provide additional insights to characterize the behavior of the pile.